Vasoprotective effects of rice bran water extract on rats fed with high-fat diet - Narongsuk Munkong (2018)
© 2016 Hainan Medical University Objective To elucidate the protective effects of rice bran water extract on the expression of endothelial nitric oxide synthase (eNOS), nuclear factor-kappa B (NF-κB), and a cluster of differentiation 36 (CD36) in the vasculature of high-fat diet-fed rats. Methods Male Sprague-Dawley rats were divided into three groups. Group I served as control, Group II was treated with high-fat diet, and Group III was treated with high-fat diet and rice bran water extract at 2 205 mg/kg/day. After four weeks, the metabolic parameters, malondialdehyde as a marker of oxidative stress, and histological features of the aorta were evaluated. The levels of transcripts and proteins in aorta were determined by real-time PCR and Western blot analysis, respectively. Results In comparison with the Group II, rice bran water extract administration resulted in a significant reduction in body weight, visceral fat tissue weights, blood glucose levels, and serum total-cholesterol and free fatty acid levels in Group III. Serum triglyceride levels tended to decrease in the Group III. Also, rice bran water extract administration obviously decreased malondialdehyde levels in both serum and aorta. Interestingly, rice bran water extract treatment demonstrated a significant up-regulation of eNOS expression and down-regulation of NF-κB p65 and CD36 expressions. Nonetheless, all groups showed normal histology of aorta. Conclusions Rice bran water extract exhibited vasoprotective effects in the high-fat diet-induced obesity condition by modulating the expression of eNOS, NF-κB, and CD36 and metabolic parameters.